TRANSFORMASI PEMBELAJARAN DIGITAL MELALUI MULTIMEDIA BERBASIS GOOGLE SITES - Musa, Muh. Azikin; N, Zulkifli; Ferdiansyah, Handy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Google Sites-assisted learning multimedia and determine its validity and practicality in science learning for tenth-grade students at MA Negeri Sidenreng Rappang. This research used a Research and Development (R&D) method with a mixed-method approach and the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects consisted of material experts, media experts, teachers, and students. Data were collected through validation sheets and practicality questionnaires. The results showed that the developed learning media was categorized as very valid with an average percentage of 92% and very practical with a percentage of 89%. Therefore, the developed learning media is feasible for use in science learning.